Perencanaan Drainase Terbuka di Simpang Nangka Kecamatan Selupu Rejang Kabupaen Rejang Lebong - Ramos Yusgima; Rezi Munizar (Journal of Science, Technology, and Innovation, 2026)
A drainage system that is unable to accommodate runoff discharge is one of the factors causing flooding, which impacts road service functionality and infrastructure sustainability. This study aims to design an open drainage system at Simpang Nangka, Selupu Rejang Subdistrict, Rejang Lebong Regency, through an evaluation of existing conditions, hydrological analysis, hydraulic capacity calculations, and the preparation of construction cost estimates. The study employed an empirical approach through field surveys, rainfall data collection, design flow analysis using the rational method, and channel capacity calculations using Manning’s equation. The results indicate that the existing channel is unable to optimally convey runoff due to limitations in its dimensions and physical condition. The design for the new channel specifies a width of 0.3 meters, a water level of 0.2 meters, and a freeboard of 0.5 meters, capable of conveying a flow rate of 0.444 m³/s. The estimated construction cost of Rp118,413,000.00 demonstrates the feasibility of implementing this design as a flood control solution based on local characteristics.